The Perception of Service Quality, Service Marketing Mix, and Appearance Mix of International Tourists: A Case of Five-Star Hotels, Pattaya Chonburi - Dangprasert, Airada; Sangsuwan, Tinikan; Ingard, Apinya (KKBS Journal of Business Administration and Accountancy, 2023)
The research studied the causal relationships between the perceptions of service quality, service marketing mix, and the appearance mix of international tourists staying at five-star hotels in Pattaya Chonburi. Quantitative research was implemented using a sample of 405 international tourists who experienced five-star hotel service. The major findings were as follows. 1) The perception of service quality in five-star hotels was at a low level (3.38). 2) The perception of service marketing mix in five-star hotels was at a low level (3.43). 3) Age, marital status, and average monthly income were significantly related to the perception of appearance mix in five-star hotels in Pattaya Chonburi. 4) The perception of service quality was significantly related to the perception of appearance mix in the decision to select five-star hotels at a moderate level (r = .735). 5) The perception of service marketing mix was significantly related to the perception of appearance mix in the decision to select five-star hotels at a moderate level (r = .763).